Let’s be pals again: major systematic changes in Palaemonidae (Crustacea: Decapoda) - De Grave,Sammy; Fransen,Charles H.J.M.; Page,Timothy J. (PeerJ, 2015)
In recent years the systematic position of genera in the shrimp families Gnathophyllidae and Hymenoceridae has been under debate, with phylogenetic studies suggesting the families are not real family level units. Here, we review the molecular evidence as well as the morphological characters used to distinguish both families, leading to the conclusion that neither family is valid. Further, we studied the structural details of the single morphological character which distinguishes the two subfamilies (Palaemoninae, Pontoniinae) in Palaemonidae, as well as their phylogenetic relationship. As the supposed character distinction plainly does not hold true and supported by the phylogenetic results, the recognition of subfamilies in Palaemonidae is not warranted. As a consequence, all three supra-generic taxa (Gnathophyllidae, Hymenoceridae, Pontoniinae) are thus herein formally synonymised with Palaemonidae.
Keywords: Molecular phylogenetics; Telson; Systematics; Synonymy; Pontoniinae; Gnathophyllidae; Hymenoceridae